Cryptochrome 1a influences source-sink partitioning during different stages of growth in tomato - D’Amico-Damião, Victor [UNESP]; dos Santos, Joel Cabral [UNESP]; Girotto, Natália Carvalho [UNESP]; Carvalho, Rogério Falleiros [UNESP] (Springer Nature, 2019)
Cryptochromes are photoreceptors that coordinate multiple processes during the plant life cycle through UV-A/blue light. In the present study, we used tomato cry1a mutant to understand how LeCRY1a influences the vegetative and reproductive development during different stages of growth. When compared to the wild type of tomato, the cry1a mutant showed greater plant height, number of leaves and leaf area during the life cycle. However, leaf pigment biosynthesis in cry1a was impaired compared with wild-type plants. Moreover, cry1a influenced the partitioning of photoassimilates between the shoot and root, mainly by positively influencing the initial root growth. Although the wild-type plants exhibited lower shoot and root biomass accumulation at the final stage of plant growth than did the mutant, the wild type exhibited higher yield, as evidenced by its greater number of ripe fruits per plant. The results reveal a complex role of cry1a throughout shoot and root growth and fruit development in tomato, causing this photoreceptor to stand out as target molecules for plant breeding programs.
Keywords: Agronomic traits; Blue-light photoreceptor; cry1a mutant; Root-to-shoot development; Solanum lycopersicum